Sharing my problems soothed my headaches and took me out of loneliness - Uwimbabazi, Berthilde (Torture Journal, 2018)
My name is Berthilde Uwimbabazi. I come from the Eastern Province, where I was born in 1960, one of 11 children of my farming parents. I married my husband in 1977. We had five children. When the genocide took place, it found us in Bugesera District. My parents, seven brothers and two of my sisters were all killed. Only one of my sisters and I escaped. However, I also lost my husband and four children. One child was killed by a neighbour. Of the children I had with my husband, I remained only with one – the one I carried on my back during the genocide. I also have another daughter as a result of the rape I experienced in 1998 and an adopted child.